The effect of application of TCA (trichloroacetic Acid) solution on Mda (Malondialdehyde) Levels in Blood in Plasma Before and After Storing at Cold Temperatures - Putjha Melati (Jurnal Teknologi dan Manajemen Pengelolaan Laboratorium, 2021)
This study aims to determine the effect of using a solution of Trichloroacetic Acid (TCA) on the levels of Malondialdehyde (MDA) in Blood Plasma before and after being stored at low temperatures. Malondialdehyde (MDA) level test was carried out using the thiobarbituric acid-reactive substance (TBARS) test method using a spectrophotometer. Data analysis was carried out statistically using the t test. The test results showed that TCA stored at cold temperatures showed more color changes compared to the use of TCA stored at room temperature which did not change color after being given a solution of Thiobarbituric acid (TBA) and heated. The value of MDA levels in samples using TCA solutions stored at cold temperatures was greater than samples using TCA solutions stored at room temperature. The results of the statistical test on the t test showed that t count > t table and p < 0.05, it was concluded that there was a significant effect and difference between samples using TCA solution stored at cold temperatures and samples using TCA solution stored at room temperature. room. From these results, further research is needed to validate the method used so that the data obtained has been validated and can be used as a reference for practicum methods and research on MDA levels at the Research Laboratory, Faculty of Medicine and Health Sciences (FKIK), Bengkulu University.